Childhood dietary patterns and later obesity: a review of the evidence. Issue 1 (26th November 2013) - Ambrosini, Gina L.
Abstract : A range of individual nutrients and foods have been suggested to increase obesity risk in childhood, but the evidence is inconsistent. Dietary patterns that summarise the whole diet may, however, be more informative. The aim of the present paper was to systematically review the current evidence pertaining to overall dietary patterns in childhood and later obesity risk. Studies eligible for review identified childhood dietary patterns using an empirical method, i.e. principal components analysis, factor analysis or reduced rank regression, and reported their prospective associations with an obesity-related outcome. Literature searches identified 166 studies and of these, seven met the eligibility criteria. Despite differences between studies, a common dietary pattern was identified in all seven studies that was high in energy-dense, high-fat and low-fibre foods. The quality of studies varied, however; the four studies reporting positive associations between this type of dietary pattern and later obesity risk were of consistently higher quality than those reporting null associations. The balance of evidence from this systematic review indicates that dietary patterns that are high in energy-dense, high-fat and low-fibre foods predispose young people to later overweight and obesity. It also highlights that examining multiple dietary factors within a dietary pattern may better explain obesity risk than individual nutrients or foods. However, more prospective studies are needed and dietary pattern research requires greater rigour and focus, to further clarify the role of dietary factors in the aetiology of obesity and inform future interventions.